Modelling the effects of herbicide dose and weed density on rice‐weed competition. (4th August 2014) - Moon, B C; Kim, J W; Cho, S H; Park, J E; Song, J S; Kim, D S; Swanton, Clarence
Summary The effects of herbicide dose on rice‐weed competition were investigated to develop a combined model, which can be utilised to estimate an optimum herbicide dose for a given weed density in paddy rice cultivation. Field studies were conducted in Suwon for rice‐Echinochloa crus‐galli competition and Iksan for rice‐Eleocharis kuroguwai during 2007. The competitive effect of the weeds E. crus‐galli and E. kuroguwai decreased with increasing doses of flucetosulfuron and azimsulfuron, respectively, in the same manner as the standard dose–response curve. The combination of the rectangular hyperbolic model and the standard dose–response curve adequately described the complex effects of herbicide dose and weed competition on rice yield. Parameter estimates were used with the model to predict rice yield and estimate the doses of flucetosulfuron and azimsulfuron required to restrict rice yield loss caused by E. crus‐galli and E. kuroguwai, respectively, to an acceptable level. For a rice yield of 5.0 t ha−1, the model recommended flucetosulfuron doses of 8.7, 13.4 and 20.1 g a.i. ha−1 when infested with E. crus‐galli at 12, 24 and 48 plants m−2 respectively. For a rice yield of 5.2 t ha−1, the model recommended azimsulfuron doses of 3.9, 7.5 and 12.6 g a.i. ha−1 when infested with E. kuroguwai at 24, 48 and 96 plants m−2 respectively. The theoretical outputs of the combined model appear robust and indicate there are opportunities for reduced herbicide use in the field. These now require evaluation under field conditions.